State of soul of a religious person. A fragment from the systematic French-Russian dictionary of religious lexis (part 1) - Nadezhda Zhukovskaia (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article continues the publication of certain parts of the Systematic French-Russian Dictionary of Religious Lexis and makes up part of the larger section Protagonistes de la religion Chrétienne, as well as of the subsection Etats d’âme de la créature humaine. In contrast to the already published topic Manifestations de la piété. Actions des fi dèles, attention is focused on the states of soul of a religious person, his spiritual seeking and moral standards. Special attention is paid to certain basic virtues, i.e. love for the fellow man, mercy, love for peace, unselfi sh generosity. As in the previous publications, not only single-standing items are given, but also common collocations usable in religious discourse, cliches, sayings typical of Orthodoxy and Catholicism which refl ect the specifi c worldview. As for the linguistic side, one should bear in mind that the Russian religious discourse often prefers more archaic utterings than French. Taking this into account, we found it possible to include not only the standard Russian equivalent, but also authored Orthodox equivalents and Church Slavonic items if they occur in authors of the 20th and 21st cc. The phrases in quotation marks not only illustrate the usage, but usually also contain a new item or demonstrate the content of a notion that is relevant to the section. They are usually made up of elements (both separate lexemes and phrases) that occur in French and Russian sources but are not quotations proper. This article was reviewed by Candidate of Theology Priest Igor Vyzhanov, the expert in comparative theology, rector of St. Nicholas Patriarch’s Cathedral in New York, and by Bruno Bisson, Candidate of Sciences in Philology, the interpreter. I am grateful to them for their meticulous reading and suggestions